Demographic pattern, clinical profile and visual outcome of patients with optic neuritis in a tertiary level eye care center of eastern Nepal - Shrestha, BG; Sharma, M; Lavaju, P; Pokharel, SM; Agrawal, N; Tulsyan, N (Health Renaissance, 2014)
Introduction: Optic neuritis is one of the common causes of sudden visual impairment. Early diagnosis and treatment with intravenous steroids can hasten visual recovery. Objective: To analyze the demographic pattern, clinical profile, and response to treatment with pulse methylprednisolone in patients presenting with optic neuritis. Methods: A hospital based retrospective analysis of records of patients with optic neuritis presenting at BPKIHS between April 2010 to February 2012 was carried out. Demographic pattern, clinical profile and visual outcome at the time of presentation and discharge were recorded. Results: Thirty-five patients (44 eyes) presented with optic neuritis. A total of 33 eyes (75%) had papillitis and 11 eyes (25%) had retrobulbar optic neuritis. Male to female ratio was 2.18:1. The mean age at presentation was 31.20 ± 17.07 years. Diminution of vision was the commonest mode of presentation. Bilateral involvement was seen in 9 patients (25.71%). The 38 eyes (86.36%) had abnormal pupillary reaction. Eight patients (22.85%) had preceeding history of trauma, 1 (2.85%) had ethmoidal sinusitis and 1 (2.85%) otitis media. At the time of discharge 32 eyes (72.7%) showed recovery in visual acuity after pulse I.V. methylprednisolone therapy. Duration at presentation, visual acuity at presentation and diagnosis did not affect the final visual outcome (p=0.486, p=0.162 and p=0.122 respectively). Conclusion: Majority of patients presented with papillitis of idiopathic origin. Most of the cases were unilateral. Most patients with visual acuity of at least perception of light or better at the time of presentation improved after pulse I.V. methylprednisolone therapy. DOI: http://dx.doi.org/10.3126/hren.v11i3.9641 Health Renaissance 2013;11(3):250-253